The relationship between achievement motivation and basketball playing skills - Rizka Antoni; Mustika Fitri (Gladi : Jurnal Ilmu Keolahragaan, 2022)
The purpose of this study is to find out the description of the motivation for high school achievement in the labschool, an overview of the skills of playing high school basketball labschool and to find out the correlation between the motivation of achieving and the skill of playing basketball. In this study, the author used the Quantitative Descriptive method by involving 20 Labschool Senior High School students. The stages of this study look at the results of data processing and discussion of research results. This research involves instrument tests in the form of questionnaire trials, validity tests and reability tests to see the correlation of achievement motivation with basketball playing skills. The conclusion of this study is that the motivation to excel and basketball skills at Labschool Senior High School is at a moderate level and there is no correlation of achievement motivation with basketball playing skills.